2013
DOI: 10.5489/cuaj.354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-frequency ultrasound combined with microbubbles on benign prostate hyperplasia

Abstract: Introduction: Our objective is to assess the effects of low-frequency ultrasound combined with microbubbles on benign prostate hyperplasia (BPH). Methods: Sixteen Beagle dogs with BPH were randomly assigned into 4 groups (n = 4): control group (without treatment), G1 group (injection with 2 mL of microbubble contrast agent); G2 group (21 kHz ultrasound); and G3 group (injection with 2 mL of microbubble contrast agent +21 kHz ultrasound). The histopathological damage to prostate cells was assessed via transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…To study dynamics of abnormal symptoms during all period of observation, patients were asked to fill in bladder diaries and record volume of urinations, information about urge episodes (UE), incontinence episodes (IE), episodes of nighttime urination (ENU) [22,23]. Patients underwent ultrasound examination of prostatic gland before the study and after treatment with Tamsulosin [24,25].…”
Section: Working Hypothesismentioning
confidence: 99%
“…To study dynamics of abnormal symptoms during all period of observation, patients were asked to fill in bladder diaries and record volume of urinations, information about urge episodes (UE), incontinence episodes (IE), episodes of nighttime urination (ENU) [22,23]. Patients underwent ultrasound examination of prostatic gland before the study and after treatment with Tamsulosin [24,25].…”
Section: Working Hypothesismentioning
confidence: 99%
“…Ultrasound has been widely used in cancer therapy and has been shown to mediate apoptosis through thermal, cavitation, sonoporation and sonochemical effects; however, the underlying mechanisms remain unclear (5). Furthermore, a number of experiments indicated that the effects of ultrasound may be enhanced by microbubbles (6,7).…”
Section: Introductionmentioning
confidence: 99%